TEI4LdoD: Textual Encoding and Social Editing in Web 2.0 Environments - António Rito Silva; Manuel Portela (Journal of the Text Encoding Initiative)
In this article we describe how textual encoding is used in our current project of constructing a digital archive of Fernando Pessoa’s Livro do Desassossego [LdoD]. Our model for virtualizing the authorial and editorial forms of this unfinished work aims to create a dynamic archive that is open to user interaction and collaboration. A brief introduction to the theoretical rationale of the archive is followed by a description of our technical solution for TEI XML encoding that is responsive to dynamic changes over time. With our software architecture proposal for processing TEI markup, the Collaborative Digital Archive of the Book of Disquiet will be able to instantiate the cooperative and social editing functionalities of Web 2.0 environments.